2022
DOI: 10.1186/s12889-022-13181-1
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and its associated risk factors among older adults in India

Abstract: Background Health at older ages is a key public health challenge especially among the developing countries. Older adults are at greater risk of vulnerability due to their physical and functional health risks. With rapidly rising ageing population and increasing burden of non-communicable diseases older adults in India are at a greater risk for multimorbidities. Therefore, to understand this multimorbidity transition and its determinants we used a sample of older Indian adults to examine multimo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
(39 reference statements)
5
20
0
1
Order By: Relevance
“…22 Khan et al determined that 83% of the older adults (age 60 years and above) in Punjab had multimorbidity. 17 Similarly, in China, Wang et al. reported that 90.5% of the rural elderly population has multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Khan et al determined that 83% of the older adults (age 60 years and above) in Punjab had multimorbidity. 17 Similarly, in China, Wang et al. reported that 90.5% of the rural elderly population has multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…22 Khan et al determined that 83% of the older adults (age 60 years and above) in Punjab had multimorbidity. 17 Similarly, in China, Wang et al reported that 90.5% of the rural elderly population has multimorbidity. 32 Aging and the presence of chronic conditions are shown to increase the occurrence of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As medical conditions improve, NCDs will be effectively treated, thus the mortality would be reduced. Meanwhile, recent studies have found that rapid urbanization in India is causing a shift in lifestyle among urban residence, with poor dietary habits mainly depending on fast-or junk food and also lower participation in the physical activity leading to higher prevalence of chronic morbidities among older adults Chauhan, Srivastava, et al, 2022;Khan et al, 2022). Hence, our finding revealed that 45+ adults belonging to urban residences have greater odds of NCD & CVD-related mortality risks than rural.…”
Section: Discussionmentioning
confidence: 57%
“…Internal diseases are their main health problems. In addition, a characteristic feature of old age is progressive multimorbidity, i.e., coexistence of several chronic diseases [ 2 ]. For the purpose of assessing this phenomenon, the concept of the so-called “major geriatric problems”, defined as “chronic disorders that gradually lead to functional incapacity and thus negatively affect the quality of life of older patients”, was introduced into modern gerontology [ 3 ].…”
Section: Introductionmentioning
confidence: 99%